PID TRAJECTORY TRACKING CONTROL FOR BALL-AND-PLATE SYSTEM - Vo, Tuan-Vu; Dang, Thai-Duong; Chung, Gia-Khang; Dang, Xuan-Truong; Ma, Thanh-Phat; Nguyen, Thanh-Lam; Dau, Nhat-Quang; Cao, Nam-Thai; Huynh, Thien-Phuc; Tong, Minh-Thong; Nguyen, Minh-Tuan; Nguyen, Hoai-Minh; Nguyen, Duc-Bao-Long (Asosiasi Peneliti Sriwijaya, 2025)
Ball-on-Plate (BoP) is developing a ball-and-beam system. This transformation transforms a single input-multi output (SIMO) system into a multi input-multi output (MIMO) under-actuated system. In this paper, we utilize the PID method—a popular linear control method in industry and academia—to track trajectory control for BoP. This system's self-made hardware is presented to test PID control through an experiment. This method is shown to track trajectory control well for real-time BoP.